6(8k+8)=0

Simple and best practice solution for 6(8k+8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(8k+8)=0 equation:


Simplifying
6(8k + 8) = 0

Reorder the terms:
6(8 + 8k) = 0
(8 * 6 + 8k * 6) = 0
(48 + 48k) = 0

Solving
48 + 48k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + 48k = 0 + -48

Combine like terms: 48 + -48 = 0
0 + 48k = 0 + -48
48k = 0 + -48

Combine like terms: 0 + -48 = -48
48k = -48

Divide each side by '48'.
k = -1

Simplifying
k = -1

See similar equations:

| 3-4x=0 | | y-4(3)=0 | | -3x+6=2 | | 64y^2+112y+49=0 | | -6=29x | | 4+7z=3z-20 | | y-3(3)=0 | | 4+7z=20-3z | | 2l+2w=264 | | 4v-5=17 | | 2l+2w=264(10w) | | (4x+8)(3x-2)=0 | | 2(0)+y=42 | | 1=y+3(y-9) | | 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 | | 10x-26=264 | | 3x-8x= | | 21b^2-114b-72=0 | | 87=5n-23 | | .12(18)+0.03x=0.06(24+x) | | 10x=264 | | 37=x+48 | | 18m^2-77m-18=0 | | 3(0)=-y+3 | | 3-8h=35 | | 13-x=-8 |

Equations solver categories